PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA SALAT BERJAMAAH DI SMK RAUDHATUL MUJAWWIDIN RIMBO BUJANG TEBO JAMBI - Irawan, Tomy Rafi; Yulia Oktarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the role of Islamic Religious Education (PAI) teachers in fostering congregational prayer at SMK Raudhatul Mujawwidin Rimbo Bujang, Tebo Jambi. The background of this research is based on the importance of habituating worship practices in schools as part of Islamic education and students’ religious character formation. Schools, especially those with pesantren-based systems, play a strategic role in cultivating discipline, spirituality, and moral values through structured religious activities. This research employed a descriptive qualitative approach with a field research design. The research subjects included PAI teachers, the school principal, and students. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The results indicate that PAI teachers play a significant role in fostering congregational prayer through role modeling, habituation, motivation, supervision, and cooperation with other teachers and dormitory supervisors. The implementation of congregational prayer has been carried out regularly, particularly for Dzuhur prayer at school and other obligatory prayers in the dormitory. Supporting factors include pesantren-based school policies, teacher commitment, and educative sanctions. Meanwhile, inhibiting factors include limited prayer facilities, technical constraints, and student discipline issues. Overall, the role of PAI teachers significantly contributes to strengthening students’ discipline and religious character through structured and consistent congregational prayer activities.